Análise da sensibilidade ao gênero do orçamento do Município de Belo Horizonte - Coutinho, Camila Mariana da Cruz Gomes (2023)
International organizations have tried to guide gender issues within the agendas for the sustainable development of nations, guiding the elaboration of gendered public policies. Despite the global efforts promoted in recent decades to eliminate inequalities between women and men, recent reports indicate that there is still much to be done, and it is suggested that the incorporation of the gender perspective in government planning instruments is fundamental for achieving effective results in the medium and long term. The study carried out sought to assess whether the budgetary instruments of the city of Belo Horizonte showed greater sensitivity to gender issues after the measures adopted for the institutionalization of gender issues. It started with the creation of a committee in 2017, responsible for coordinating work on the elaboration of the City Gender Equity Plan, officially launched in 2019 by the institution. Gender- Sensitive budget allocations were selected from the 2018 to 2022 budgets, whose treatment and analysis revealed a slight increase in sensitivity to gender issues in the municipality, even though the actions of the plan have not been properly incorporated into the planning instruments of short and medium term, highlighting the difficulties related to translating the plan into budget allocations.